Algebra

posted by Bretagne

How would i complete these problems?

1. (√6mn)^5

2. ^3√16x - ^3√2x^4

3.^4√x • ^3√2x

4. ^3√72x^8

5. √63a^5b • √27a^6b^4

and are these problems correct?

6. √2025xy/3√3 = 15√xy/√3

7. 3√18 + 8√50 = 49√2

8. √12 • √135 = 18√5

1. Guido

The way you typed your questions is not clear. Please use proper keyboard symbols.

2. Damon

6, 7 and 8 are correct.

easier to write sqrt as fractional power for these
like sqrt (x) = x^(1/2)
1.
{(6 n m )^.5}^5 = (6 m n)^(5/2)
= (6 m n)^4/2 * (6 m n)^1/2
= 36 m^2 n^2 sqrt(6 m n)
2.
(16x)^1/3) - (2x^4)^1/3 = 2 (2)^1/3 (x)^1/3 - 2^1/3 x^4/3
= 2^1/3 x^1/3( 2 - x)
3.
x^1/4 2^1/3 x^1/3
= 2^1/3 x^7/12
4.
72^1/3 x^8/3
(2^3 * 3^2)^1/3 x^8/3
2 (9)^1/3 x^8/3
5.
(3*3*7 *a^5 * b^1 *3^3 * a^6* b^4)^1/2
= (3^5 a^11 b^5)^1/2
= 9 a^5 b^2 (3 a b)^1/2

Similar Questions

1. Math

Find an equation of the line that bisects the obtuse angles formed by the lines with equations 3x-y=1 and x+y=-2. a. (3√2 +√10)x-(√10 + √2)y-2√10+√2=0 b. (3√2 - √10)x+(√10 - √2)y+2√10+√2=0 …
2. maths

I will be thankfull to you if you help me to solve the below problem: 6√x-11/3√x=2√x+1/√x+6 I tried to solve the above problem like this: (6√x-11)(√x+6)=(3√x)(2√x+1) 6√x(√x+6)-11(√x+6)=(3√x)(2√x)+(3√x)(1) …
3. Algebra

Simplify the expressions and solve the equations 1. 2√3 - √12 My answer: 2√3 - 2√3 = 0 2. √(5p + 5)^2 = √(6p + )^2 I got the answer p = 4 3. √(28) + √(63) + √(175) This one seems …
4. Algebra Work Check

1. 5√6 * 1/6√216 5/6 * √1296 5/6 * √144 * √9 = 30 2. -9√28a^2 * 1/3√63a -3√1764a^3 -3√49a^2 * √36a -3*7a*6√a = -126a√a

Simplify by rationalizing each denominator. 1. 2/√3 A: 2√3 / 3 2. -18/√6 A: -3√6 Add or subtract. 3. 4√3 - 9√3 A: -5√3 4. √8 - 15√2 A: -13√2 5. √45 + √20 A: 5√5 …